Causal Factor Influencing Electoral Voting - Siriphanit, Jirawat; Kenaphoom, Assoc. Prof. Dr. Sanya Kenaphoom; Kosolkittiamporn, Assoc. Prof. Dr. Saowaluk (Journal for Developing the Social and Community, 2018)
Individual person must has reason to make political decision in manner that will give him maximum satisfaction under certain level of limitation, thus, the political behavior is based on rational decision. Therefore, factors influencing political decision making are political utility; the election is a political behavior depends on political utility as well. It is external stimulus from political activity and/or political actor which based on 4 theories; Deterministic theories, Psychology Theories, Exchange Theory and Consciously Rational Theories.